Changes in Diet, Sleep, and Physical Activity Are Associated With Differences in Negative Mood During COVID-19 Lockdown - Ingram, Joanne; Maciejewski, Greg; Hand, Christopher J. (Frontiers in Psychology, 2020)
The UK and Scottish governments instigated a societal lockdown in response to the COVID-19 pandemic. Subsequently, many experienced substantial lifestyle changes alongside the stresses of potentially catching the virus or experiencing bereavement. Stressful situations and poorer health behaviours (e.g., higher alcohol consumption, unhealthy diet, poorer sleep quality, physical inactivity) are frequently linked to poor mental health. Our objective was to examine changes in health behaviours and their relationship with negative mood during COVID-19 lockdown. We also considered associations between health behaviours and socio-demographic differences and COVID-19-induced changes. 399 participants completed a questionnaire asking about their personal situation and health behaviours during lockdown as well as a negative mood scale. The significance threshold for all analyses was α=.05. Poorer diet was linked to more-negative mood, and to changes to working status. Poorer sleep quality was linked with more-negative mood, and with ‘shielding’ from the virus. Being less physically active was related to more-negative mood and student status, whereas being more physically active was linked to having or suspecting COVID-19 infection within the household. Increased alcohol consumption was linked to living with children, but not to negative mood. Changes to diet, sleep quality, and physical activity related to differences in negative mood during COVID-19 lockdown. This study adds to reports on poor mental health during lockdown and identifies lifestyle restrictions and changes to health behaviours which may, to some extent, be responsible for higher negative mood. Our data suggests that it is advisable to maintain or improve health behaviours during pandemic-associated restrictions.